Respuesta :
[tex]k = \frac{2b - 5w}{3k}[/tex]
[tex]3k^{2} = 2b - 5w[/tex]
[tex]3k^{2} + 5w = 2b[/tex]
[tex]5w = 2b - 3k^{2}[/tex]
[tex]w = \frac{2}{5}b - \frac{3}{5}k^{2}[/tex]
[tex]3k^{2} = 2b - 5w[/tex]
[tex]3k^{2} + 5w = 2b[/tex]
[tex]5w = 2b - 3k^{2}[/tex]
[tex]w = \frac{2}{5}b - \frac{3}{5}k^{2}[/tex]
Answer:
b = [tex]\frac{2b - 3k^{2} }{5}[/tex]
Step-by-step explanation:
To solve for w in this equation;
k = [tex]\frac{2b - 5w}{3k}[/tex]
This implies we have to make w the subject of the formula.
To make w subject of the formula, first we cross multiply.
3k × k = 2b - 5w
3k² = 2b -5w
Now we will subtract 2b from both- side of the equation
3k² - 2b = -5w
we want to make the right hand side of the equation positive, to do that , we will just multiply through by minus sign. The equation becomes;
-3k² + 2b = 5w
We can rearrange the equation;
2b - 3k² = 5w
5w = 2b - 3k²
Then we will now divide both-side of the equation by 5
[tex]\frac{5w}{5} = \frac{2b - 3k^{2} }{5}[/tex]
In the left side of the equation, the 5 at the numerator will cancel out the 5 at the denominator.
Hence;
w = [tex]\frac{2b - 3k^{2} }{5}[/tex]